Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Rumah Makan Moeslim Chicken Di Mendungan Kartasura - Nurdiansyah, Jemy, Drs. Sujadi, M.M (2015)
This study aims to determine the effect of service quality dimensions comprising Reliability, Responsiveness, Assurance, Empathy, and Tangible partially and simultaneously to customer satisfaction Moeslim home eating chicken in mendungan Kartasura.The population in this study is the customers who visit the restaurant Moeslim chicken in mendungan Kartasura. Samples taken as many as 100 respondents using the technique of Non-Probability Sampling with convenience sampling approach, the sampling is based on the availability and ease of elements to get it. In this study using multiple regression data analysis and hypothesis testing using t statistical test, a statistical test F, and the coefficient of determination. Reliability analysis of the results obtained by the variable t value 5.304 with significance 0.000 <0.05 so Reliability positive and significant impact on customer satisfaction. Responsiveness variable analysis results have t value of 3.008 with a significance level of 0.003 <0.05 so Responsiveness positive and significant impact on customer satisfaction. Assurance variable analysis results have t value of 2.321 with 0.022 significance level <0.05 so Assurance positive and significant impact on customer satisfaction. Emphaty variable analysis results have t value of 2.234 with 0.028 significance level <0.05 so Emphaty positive and significant impact on customer satisfaction. Tangibles variable analysis results have t value of 2.466 with 0.015 significance level <0.05 so Tangibles positive and significant impact on customer satisfaction. Results showed simultaneously (simultaneously) variable Reliability, Responsiveness, Assurance, Empathy, and Tangible with tingkan significance 0.000 <0.05 so simultaneously (simultaneously) significantly affects customer satisfaction. Adjusted R-square values ​​obtained at 0.458 or 45.8% customer satisfaction can be explained by the variable Reliability, Responsiveness, Assurance, Empathy, and Tangible while 54.2% is explained by other variables not examined in the study.